THE IMPORTANCE OF SLEEP AND THE CONSEQUENCES OF SLEEP DEPRIVATION - Dominika Walczak; Adrian Kruk; Aleksander Białoń; Weronika Ewa Nowak; Paweł Harbut; Lidia Jurczenko; Igor Gawłowski; Aleksandra Dorosz; Katarzyna Jakubowska; Aleksandra Miśta (International Journal of Innovative Technologies in Social Science, 2025)
Sleep is a fundamental biological process regulated by the circadian rhythm and is governed by complex neural mechanisms involving various brain regions and neurotransmitters. It consists of non-rapid eye movement (NREM) and rapid eye movement (REM) stages, each playing a distinct role in physiological and cognitive restoration. One leading theory, the Synaptic Homeostasis Hypothesis, suggests that sleep serves to rebalance synaptic strength accumulated during wakefulness, thereby preserving cognitive efficiency and promoting memory consolidation. Optimal sleep varies with age and is essential for maintaining physical, cognitive, and emotional health. However, modern lifestyles, characterized by increased screen time, irregular schedules, and a 24/7 work culture have contributed to widespread sleep deprivation, particularly among adolescents, shift workers, and high-demand professionals. Sleep deprivation, whether partial or total, is linked to a wide range of adverse health outcomes, including obesity, cardiovascular disease, cognitive decline, and increased accident risk. Chronic sleep deprivation also significantly impacts executive function and has been associated with sleep disorders such as obstructive sleep apnea, which further exacerbate health risks. Objective measures like actigraphy and EEG provide valuable insights into sleep quality and fragmentation beyond self-reported duration.